Probing synergistic outcome of graphene derivatives in solid-state polymer electrolyte and Pt-free counter electrode on photovoltaic performances. (15th September 2020) - Kumar, Sanath; Manikandan, V.S.; Panda, Subhendu K.; Senanayak, Satyaprasad P.; Palai, Akshaya K.
Highlights: Introduction of S-rGO into polymer blend ensued 30-fold boost in ionic conductivity. Filler added polymer electrolyte resulted decrease in crystallinity by 2 times. Fabricated polymer based solid-state Pt free DSSC exhibited PCE of 4.24%. Abstract: Enhancing the conductivity of polymer electrolytes in DSSC has evolved as an important strategy to enhance the efficiency of the DSSC. In this context, we have synthesized a range of graphene based derivatives which when incorporated into a polymer electrolyte enhances the ionic conductivity of PEO/PVDF-HFP polymer electrolyte by 30 times reaching a maximum value of 3.07 × 10 −4 S/cm. Devices fabricated from these modified solid state electrolyte exhibited a photo-conversion efficiency of upto 4.24% which is comparable to the efficiency magnitude observed in liquid electrolyte based DSSC fabricated under similar condition at our laboratory. Detailed structural, microscopic and morphological characterization attributed this enhancement in the electrochemical performance to a combination of factors such as reduced crystallinity of the polymer electrolyte membrane, development of smooth non-porous structure and increased chemical interaction between the lamellar structure.